COMPARATIVE ASSESSMENT OF THE AVERAGE YIELD OF FRUIT IN THE MEMBER STATES OF THE EUROPEAN UNION FOR THE PERIOD FROM 1961 TO 2014 - Nelly Keranova (Science & Research, 2018)

(untitled)
The objective of this work is to group and assess the Member States of the European Union according to the average yield of citrus, pome and stone fruits for the period 1961-2014. The EU countries are grouped through hierarchical cluster analysis based on the average yield of the respective fruit. The purpose is achieved also through a single-factor analysis of variance (ANOVA) by the Duncan criterion. By this analysis a comparative assessment of the EU member states is made. It was found that the country with the highest average yield of citrus fruits is Italy (140112,63 hg /ha), followed by Spain (106111,58 hg/ha) and the lowest – Cyprus (8715,46 hg/ha). The country with the highest average yield of fresh fruit is Ireland (101670,7 hg/ha), second, but with a significant difference is Romania (75700 hg/ha), and the country with the lowest yield is Latvia (12938,78 hg/ha). Italy (109746,17 hg/ha) and Bulgaria (92132,59 hg / ha) have the highest average yields of stone fruits and the country with the lowest yield is Spain (6821,8 hg/ha).